2018
DOI: 10.11606/issn.2176-7262.v50i6p358-364
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha -308 promoter polymorphism and insulin resistance inoverweight and obese adolescent

Abstract: Study Model/Methodology: This is a cross-sectional study with a sample of 104 overweight/obese adolescents, with a mean weight of 52.98 kg ± 22.00, mean age 16.01 ± 2.91 years. We used the homeostasis model assessment-estimated IR (HOMA-IR) index to quantify the insulin resistance (IR). The -308 polymorphism of the promoter of TNF-α was performed using polymerase chain reactionrestriction fragment length polymorphism technique. Statistical analysis of the quantitative measures was conducted with a student’s t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Other studies have also found that AA and GA genotypes are more common in male obese individuals, whereas in female individuals AG genotype is associated with a higher risk of obesity. 71 In another study in Brazil, -308G/A polymorphism in TNF-α promoters, A allele, GA, and AA genotypes contribute to increased insulin resistance and excess body weight in adult. 73 In the Javanese population, this gene polymorphism showed that GA genotype patients have lipid and TNF-α levels higher than the GG genotype, and variation of -308 G/A TNF-α gene plays a role in a higher risk of obesity, 74,75 risk of breast cancer, 76 hypertension, 77 and inflammatory bowel disease.…”
Section: Tnf-αmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have also found that AA and GA genotypes are more common in male obese individuals, whereas in female individuals AG genotype is associated with a higher risk of obesity. 71 In another study in Brazil, -308G/A polymorphism in TNF-α promoters, A allele, GA, and AA genotypes contribute to increased insulin resistance and excess body weight in adult. 73 In the Javanese population, this gene polymorphism showed that GA genotype patients have lipid and TNF-α levels higher than the GG genotype, and variation of -308 G/A TNF-α gene plays a role in a higher risk of obesity, 74,75 risk of breast cancer, 76 hypertension, 77 and inflammatory bowel disease.…”
Section: Tnf-αmentioning
confidence: 97%
“…Activation of the immunologic system during infection or injury causes metabolic changes. 71 TNF-α is expressed on the surface of transmembrane protein cells and is involved in the pathogenesis of various inflammatory diseases. The TNF-α gene is located on chromosome 6.p21.1-21.3.…”
Section: Tnf-αmentioning
confidence: 99%